Establishments' use of temporary agency workers: the influence of institutions and establishments' employment strategies. Issue 18 (11th October 2017) - Allen, Matthew M. C.; Liu, Jiajia; Allen, Maria L.; Imran Saqib, Syed
Abstract: Comparative institutional analyses have added much to our understanding of HRM in different countries, providing powerful arguments against the need for flexible labour markets to boost economic performance. However, existing research has tended to downplay the possibility that variation within countries may result in a well-protected core of workers that grows ever smaller alongside increasing numbers of precarious workers. We draw on data from the World Economic Forum and the European Company Survey to examine how institutions influence establishments' use of temporary workers in 29 European countries plus Turkey. We analyse the data using (1) principal components analysis to categorize the countries in our analysis, (2) a two-step cluster analysis to draw up groups of establishments by their use of temporary workers and (3) a multilevel logistic regression to examine how the institutional setting of establishments and key establishment characteristics interact to influence workplaces' use of temporary workers. We show that institutional characteristics shape the prevalence of temporary workers in the 28 European Union member states plus FYR Macedonia and Turkey; however, institutions are not deterministic and important variation in the use of temporary workers depends upon the interaction between establishment characteristics and the establishment's business system.